Peran Orang Tua Dalam Mendampingi Anak Pada Proses Pembelajaran Pendidikan Agama Islam Selama Pandemi Covid 19 - Aulia, Shelanita; Meutia, Zya Dyena (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The Covid-19 phenomenon around the world is getting worse day by day. The covid 19 pandemic has put the world's economy in uncertainty. However, not only in the economic sector, one of the effects of this pandemic is also being felt in the education sector. Students and school have been sent home and closed. Therefore, learning must be done at home. Teachers are confused about finding the right learning method for students, then they have to ask parents for help in learning. A new problem resurfaced. Parents struggle to manage work and childcare. Moreover, Islamic Education, which must be really ascertained whether you already understand or not will have a big impact in the future. This study aims to see how the role of parents in accompanying children in learning Islam at home. Qualitative research methodology using exploratory study case method. In this study, respondents were 8 parents of students in various schools in Banyuasin. Interviews were conducted semi-structured with a list of questions compiled for interviews developed based on related literature. Respondents were selected using a purposive method. The results of this study are that there are several impacts or safety as parents and students in online teaching and learning activities and the application of face-to-face learning zoning in schools are ineffectiveness in the learning process, especially regarding the implementation of practices in Islamic education, lack of using technology and additional work for parents. in accompanying children and the limited knowledge of parents in Islamic Education.